Land tenure, autonomy and crop choice: Institutional drivers of agricultural diversification in Uzbekistan - Muhammad Bilal; Pishenbay Umirbekov; Nodir Djanibekov; Abdusame Tadjiev; Bakhrom Mirkasimov (Agricultural Systems, 2026)
CONTEXT: Crop diversification can improve income stability, reduce environmental risks, and make farming more resilient. Uzbekistan is one such country, where agriculture is shifting from a state-controlled cotton and wheat system towards a more market-oriented approach. This study explores how crop diversification is linked to institutional factors, such as farmers' sense of land security and their ability to make independent decisions. OBJECTIVE: The study aims to understand how the variety of crops grown by farmers is related to their perceptions of land tenure security and decision-making autonomy. It also considers how training, information sources, and farm characteristics are associated with diversification outcomes. METHODS: Using survey data from 450 farms in the Samarkand province collected in 2022, the study measures crop diversification with Simpson's Diversity Index and groups farms into low, medium, and high diversification levels. A heteroscedastic ordered probit model is applied to examine how institutional, geographic, and socio-economic factors are associated with these outcomes. RESULTS AND CONCLUSIONS: Farmers who feel confident about keeping their land and who report greater freedom in deciding what to grow are more likely to have diversified crop portfolios. Attending more training programs and using land as an incentive for farm workers are also positively linked to diversification. In contrast, relying on media for agronomic information and having formal agricultural education focused on traditional crops are associated with lower diversification. Larger farms tend to avoid monoculture but are not necessarily more likely to achieve high diversification. SIGNIFICANCE: These findings suggest that improving land tenure security, expanding farmer autonomy, increasing access to diverse training, and providing better-targeted farming advice can help support the shift towards more diverse and sustainable farming. This has important implications not only for Uzbekistan, but also for other countries undergoing agricultural reform.
Keywords: 630; crop diversification; decision-making autonomy; institutional factors; land tenure security; heteroscedastic ordered probit